2022
DOI: 10.3390/jof8080837
|View full text |Cite
|
Sign up to set email alerts
|

Circumfusicillium cavernae gen. et sp. nov. (Bionectriaceae, Hypocreales) Isolated from a Hypogean Roman Cryptoporticus

Abstract: Stone monuments and relics are prone to biodeterioration processes prompted by microbial proliferation and activity. Among the distinct microbes capable of stone colonization, fungi are known to strongly contribute to stone biodeterioration. During the ongoing efforts aiming to study fungi thriving in dolomitic limestone walls of the Coimbra’s hypogean Roman cryptoporticus (Portugal), two unknown Bionectriaceae isolates were retrieved. The aim of this work was to depict the molecular and phenotypic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Bionectriaceae mainly includes Bionectria apocyni , Bionectria oblongispora , Bionectria pseudostriata , and Bionectria Sesquicillii , and so forth. Bionectriaceae are mainly parasitic or saprophytic on dead branches and leaves, 45 even some Bionectriaceae can degrade stones 46 . The results indicated that Bionectriaceae could consume PLA composites as the carbon sources.…”
Section: Resultsmentioning
confidence: 97%
“…Bionectriaceae mainly includes Bionectria apocyni , Bionectria oblongispora , Bionectria pseudostriata , and Bionectria Sesquicillii , and so forth. Bionectriaceae are mainly parasitic or saprophytic on dead branches and leaves, 45 even some Bionectriaceae can degrade stones 46 . The results indicated that Bionectriaceae could consume PLA composites as the carbon sources.…”
Section: Resultsmentioning
confidence: 97%
“…Nutrient-rich media, such as PDA, tend to favor common fungal generalists that grow rapidly, often outgrowing more specialized species, and although they are com- From the 36 identified species, Acremonium alternatum, Arthrinium marii, Aspergillus conicus, Aspergillus fumigatus, Cladosporium dominicanum, Cladosporium floccosum, Cyphellophora olivaceae, Hansfordia pulvinata, Microascus cirrosus, Microscypha sp., Neophysalospora eucalypti, Penicillium corylophilum, Penicillium echinulatum, Penicillium olsonii, Phlebiopsis gigantea, Stachybotrys chartarum, Talaromyces purpureogenus, Toxicocladosporium irritans and Ustilago cynodontis are first reports, not only for Ançã limestone monuments, but for limestone monuments in general [37,62]. Additionally, this is the first time that Aeminium ludgeri and Circumfusicillium cavernae, two newly described species of Portuguese heritage, have been detected and isolated from a new different site (Figure S1) [63,64].…”
Section: Influence Of Culture Media On Species Richnessmentioning
confidence: 88%
“…The following supporting information can be downloaded at https: //www.mdpi.com/article/10.3390/app122010650/s1, Table S1: Identification of all fungal isolates retrieved in this study. Figure S1: Isolates of two newly described species (a) Circumfusicillium cavernae (Bionectriaceae), (b) C. cavernae colony in detail and (c) Aeminium ludgeri (Aeminiaceae), (d) A. ludgeri colony appearance after starting maturing, on PDA, first described in deteriorated limestone in Coimbra (Portugal) and isolated in the present study [63,64]. Institutional Review Board Statement: Not applicable.…”
Section: Supplementary Materialsmentioning
confidence: 99%